Xanthophyll cycling and fucoxanthin biosynthesis in the model diatom Phaeodactylum tricornutum: recent advances and new gene functions - Giossi, Chiara E.; Kroth, Peter G.; Lepetit, Bernard (Frontiers in Photobiology, 2025)
Diatoms, heterokont microalgae found in all aquatic habitats, can be distinguished by their typical brown colour due to the presence of a characteristic light-harvesting carotenoid: fucoxanthin. The biosynthesis of fucoxanthin involves several intermediates, some of which also play a key role in photoprotection via the xanthophyll cycle, controlling the dissipation of excessively absorbed light energy in the form of Non-Photochemical Quenching (NPQ). The regulation of the fucoxanthin pathway is therefore crucial to direct xanthophyll biosynthesis towards light harvesting or photoprotective functions. Yet, until recent years most of the steps in this key metabolical route remained unknown. Interestingly, diatoms possess multiple homologs of the ancestral genes encoding the two xanthophyll cycle enzymes: Violaxanthin De-Epoxidase (VDE) and Zeaxanthin Epoxidase (ZEP). Here, we review the recent discoveries of the function of most VDE and ZEP isoforms in the fucoxanthin pathway of the model diatom Phaeodactylum tricornutum. Some of these enzymes have a central role in photoprotection, while other have been identified as ideal targets for engineering and industrial applications. We discuss the physiological role of these proteins and address missing links in the pathway and unknown properties of these enzymes. Finally, we argue that the expansion of the VDE and ZEP gene families represented a turning point in the evolution of xanthophyll cycling and fucoxanthin biosynthesis in diatoms.